Pick, Mix or Match? A Discussion of Theories for Management Accounting Research - Maleen Z. Gong; Michael S. C. Tse (Journal of Accounting, Business and Management (JABM), 2009)
This paper presents a review on applications of four types of theories for management accounting (MA) research (contingency theory, agency theory, sociological theories and psychological theories) and comments on prospects of combining multiple theories in future MA research. Based on a review of studies that adopted the four types of theories, the authors argue that multiple theories can be applied jointly in future research to enrich our understandings on MA practices from multiple perspectives. However, theories should maintain their distinctiveness in their applications. Blending multiple theories into a single all-purpose theory can be counterproductive due to loss of explanatory power.